A baseline study on diversity of birds in Sani Bheri River Valley, Nepal - Shrestha, Ganga; Shrestha, Mohan Bikram; Byanju, Rejina Maskey; Reule, Swabhiman; Oli, Sundar (Nepal Journal of Environmental Science, 2021)
Rivers and lakes are important habitats for both resident and migratory wetland-dependent birds. This paper presents the study of birds’ seasonal diversity in Sani Bheri River Valley, outside the protected areas of Nepal. The study was carried out from 8-17 March 2019 (Spring) and 12-21 October (Autumn) 2019 covering a 52 km river stretch from Naighat (upstream area where Pelma River and Uttarganga River mix and flow as Sani Bheri river) to Remnaghat (downstream towards the confluence with Thuli Bheri) using the Mackinnon Listing method. The present study recorded 851 occurrences belonging to 11 Orders, 33 Families, and 71 bird species. Order Passeriformes (52 species) and family Muscicapidae (13 species) were dominant. Plumbeous Water-redstart (Phoenicurus fuliginosus) had the highest relative abundance (7.64%). Shannon-Weiner diversity index (H’= 3.61) and Evenness index (e= 0.85) indicate the diverse assemblage of avian fauna in the study area. This study showed that Sani Bheri River Valley provides the habitat for one globally threatened, four nationally threatened, and eight species listed in Appendix-II of CITES. The results provide the baseline information on avian species, which can provide a good database and can be incorporated in conservation implications.